Вариации относительного содержания молекулярных ионов в зависимости от сезона и магнитной активности - Григоренко, Е. И.; Живолуп, Т. Г.; Таран, В. И. (НТУ "ХПИ", 2003)
In this paper the theoretical model for the lower part of the F layer of ionosphere is presented. This model enables to calculate the absolute and relative concentrations of the molecular ions. The altitude-temporal variations of the ion composition for summer and winter are described. The variations of the transition height from molecular ions to atomic oxygen ions during the magnetic storm are considered
Keywords: ионосфера; атомарный кислород; радар; сезонная аномалия